Photo-controlled patterned wrinkling of liquid crystalline polymer films on compliant substrates. (February 2018) - Fu, Chenbo; Xu, Fan; Huo, Yongzhong
Highlights: A novel approach to generate surface wrinkles via photo-induced instability was proposed. Geometric and size effects of photo illuminations on the buckling and post-buckling pattern evolution were carefully explored. Phase diagrams were provided to guide the photo design of surface patterns. A variety of wrinkling morphologies including wavy shaped, ring-like, checkerboard, stripe, herringbone and hybrid patterns were obtained. A simple and flexible way to design various wrinkling patterns through changing shielding plates is suggested. Graphical abstract: Abstract: Photo-chromic liquid crystalline polymer (LCP) is a type of smart materials which are sensitive to light. Here we harness its photo-mechanical response to flexibly control surface patterning, through modeling a film involving homeotropic nematic liquid crystals with director perpendicular to the polymer film attached on a compliant substrate. Theoretical and numerical analyses were conducted to explore the surface instability of such film/substrate systems under both uniform and non-uniform illuminations by ultraviolet (UV) light, respectively. By minimizing energy, the film can buckle into checkerboard patterns at the critical photo load. Fourier spectral method is applied to study the post-buckling evolution of various 3D wrinkling patterns including wavy shaped, ring-like, checkerboard, stripe and herringbone patterns. Besides, non-uniform illumination is investigated through square and circular patterned lights, respectively, where the wrinkles can be ordered and controlled remotely and flexibly. Furthermore, the geometric and size effects of local illumination are discussed and characterized by some critical dimensionless parameters. Phase diagrams are provided and agree with experimental observations, which could be used to guide the photo design of wrinkling morphogenesis that is particularly attractive for remote control applications.